Conformal surface intensive doping of low-valence Bi on Cu2O for highly efficient electrochemical nitrate reduction to ammonia production - Phu, Thi Kim Cuong; Hong, Won Tae; Han, Hyungu; Song, Young In; Kim, Jong Hun; Roh, Seung Hun; Kim, Min-Cheol; Koh, Jai Hyun; Oh, Byung-Keun; Kim, Jun Young; Chung, Chan-Hwa; Lee, Dong Hyun; et al. (Elsevier BV, 2024)
Electrochemical nitrate reduction reaction (NO3RR) has been regarded as a promising alternative to the Haber-Bosch process for sustainable and clean NH3 production. To develop highly active and stable electrocatalysts for NO3？ to NH3 production, Cu-based materials have been considered as potential candidates owing to the excellent NO3？ adsorption to easily overcome the rate determining step of nitrate to nitrite conversion in NO3RR, although the poor NH3 yield rate is still challenging. In this study, we report a hybrid electrocatalyst with Bi dopant substitutionally incorporated on cuboctahedra Cu2O platform (Bi/Cu2O) via in-situ hydrothermal method. The Bi/Cu2O shows the NH3 yield rate of 2562.56 μg h？1 mgcat-1 and Faradaic efficiency of 99.2 % at ？0.8 V versus reversible hydrogen electrode in a neutral electrolyte, which is the highest performance among previously reported Cu-based electrocatalyst for NO3RR to NH3. The interfacial synergetic effect of sufficient protonation from Bi-doped overlayer and efficient NO3？ adsorption from the Cu2O platform results in excellent NO3RR performance. The experimental variable investigations with in-situ attenuated total reflectance-Fourier transform infrared measurement elucidate that not only nitrate to nitrite conversion but also the protonation of *NO2 is the rate limiting step for NH3 production.